Interrelated influence of light and Ni on Trichodesmium growth - Ho, Tung-Yuan; Chu, Tse-Hua; Hu, Cheng-Ling (Frontiers in Microbiology, 2013)
Our previous laboratory study revealed that insufficient Ni supply can limit nitrogen fixation in Trichodesmium, a primary diazotrophic phytoplankton in the tropical and subtropical oceans. Here we show that light intensity and Ni availability interrelate to influence Trichodesmium growth. Trichodesmium growth is severely inhibited under high light (670 uE m-2 s-1) and insufficient Ni condition. On the contrary, the sufficient supply of Ni in seawater can sustain the growth of Trichodesmium under either high or low light conditions. We also observed elevated intracellular Ni uptake in Trichodesmium grown under relatively high light condition, supporting that the Ni requirement is used for removing superoxide generated through photosynthetic electron transport. This study shows that light saturation condition for Trichodesmium growth is Ni concentration dependent. This finding may exhibit implications for interpreting temporal and spatial distributions and activities of Trichodesmium in both modern and ancient oceans when light intensity and Ni concentrations have significantly varied.